Co9S8/CoS@S, N co-doped porous carbon derived from MOFs as an efficient catalyst for the oxygen evolution reaction. (January 2021) - Wang, Shun; Zhou, Gaoliang; Lv, Jianguo; Ma, Yuxuan; Wang, Ying; Hu, Changjuan; Zhang, Junjun; Yang, Jin; He, Gang; Zhang, Miao; Zhao, Min; Chen, Xiaoshuang; et al.
Abstract: Co9 S8 /CoS@S, N co-doped porous carbon were successfully prepared by using thiourea and Co-based metal organic frameworks (Co-MOFs) as precursor and template. The porous carbon with a large surface area provides a favorable transport environment for the electrons and ions in the electrolyte. Co9 S8 /CoS nanoparticles and S doping may reduce the Ohmic series resistance (Rs ) and charge transfer resistance (R ct ) of the electrocatalysts. The prepared Co-1.8/NC-0.3 composite shows excellent electrocatalytic performance for oxygen evolution reaction (OER) with a low overpotential of 180 mV at 10 mA cm −2 and high durability in 1 M KOH solution. The R ct and Rs values of Co-1.8/NC-0.3 are 5.01 × 10 −6 and 1.72Ω. The lowest R ct indicates that the catalysts has lower resistance and more OER activities at the electrode/electrolyte interface in comparison with the other catalyst. Highlights: A simple route was used to prepare Co9 S8 /CoS@S, N co-doped porous carbon. The Co-1.8/NC-0.3 possessed mesopores and micropores structure as well as low charge transfer resistance. The Co-1.8/NC-0.3 composite delivered excellent OER catalytic activities and stabilities.